Optimization of Vascular Supply in Free Flaps for Head and Neck Reconstruction: Analysis of a Young Team’s Experience - Iacoviello, Paolo; Bacigaluppi, Susanna; Callegari, Simone; Rossello, Carlo; Antonini, Andrea; Gramegna, Marco; Da Rold, Mariano; Signorini, Giuseppe; Verrina, Giuseppe (Frontiers in Surgery, 2022)
Background For head and neck reconstructive procedures, free flap survival depends on microsurgical and anatomical choices besides multimodal clinical management. The aim of the present study was to identify relevant variables for flap survival in our initial consecutive series. Methods A single center, novel reconstructive team consecutive surgical series had been revised. Outcome was analyzed in terms of flap survival observing variables considered more relevant: flap type, recipient artery, vein(s) and graft interposition were discussed for facial thirds to be reconstructed. Statistical analysis was performed with Chi-square, Mann-Whitney and Odds ratio. Results 118 free flaps were performed in 115 microsurgical procedures (93.9% for malignancies) on 109 patients, with a flap survival rate of 91.5%. For reconstruction of middle and lower third of the face the facial artery was privileged, because already transected during lymph-node dissection in order to save the superior thyroid artery for further microsurgical needs. Flap failure was 50% venous. Double vein anastomosis was not related to flap survival. Deep venous drainage (as the internal jugular vein system) required fewer revisions. Half of re-explorations saved the flap. Grafts were a risk for flap survival. Bony flaps were more critical. Conclusion At comparable reconstructive quality, flap choice should avoid a vascular graft. The facial artery is a preferable recipient vessel, since it saves other arteries both in the case of an arterial revision and in the case of recurrence, for further free flap reconstruction. For venous anastomosis a deep venous recipient is safer since it offers the possibility to choose the level of anastomosis optimizing the vascular pedicle geometry. A close post-surgical flap monitoring is advisable up to 7 days postoperatively to allow for timely flap salvage.